1999
DOI: 10.1124/mol.56.5.1014
|View full text |Cite
|
Sign up to set email alerts
|

Tight Association of the Human Mel1a-Melatonin Receptor and Gi: Precoupling and Constitutive Activity

Abstract: If stably expressed in human embryonic kidney (HEK)293 cells, the human Mel(1a)-melatonin receptor activates G(i)-dependent, pertussis toxin-sensitive signaling pathways, i.e., inhibition of adenylyl cyclase and stimulation of phospholipase Cbeta; the latter on condition that G(q) is coactivated. The antagonist luzindole blocks the effects of melatonin and acts as an inverse agonist at the Mel(1a) receptor in both intact cells and isolated membranes. This suggests that the Mel(1a) receptor is endowed with cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
1
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 32 publications
7
73
1
3
Order By: Relevance
“…G i has been shown to be precoupled to MT 1 in its inactive form and to remain stably associated upon agonist stimulation despite the presence of high GTP concentrations in intact cells (29,36). Destabilization of the MT 1 -G i complex in the absence of MUPP1 has different effects on the signaling capacities of MT 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…G i has been shown to be precoupled to MT 1 in its inactive form and to remain stably associated upon agonist stimulation despite the presence of high GTP concentrations in intact cells (29,36). Destabilization of the MT 1 -G i complex in the absence of MUPP1 has different effects on the signaling capacities of MT 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that high affinity agonist binding to MT 1 depends on the coupling of the receptor to G i proteins (36). Accordingly, decreased high affinity agonist binding would be expected when MUPP1 is displaced from MT 1 .…”
Section: G I Coupling and High Affinity Agonist Binding To Mt 1 Depenmentioning
confidence: 99%
“…Crude Membrane Preparation, Solubilization, and Immunoprecipitation-Crude membranes were prepared, solubilized with 1% digitonin, a detergent known to maintain MTR in a native conformation, and immunoprecipitated as described recently (13,14) with 10 g/ml of the FLAG-specific M2 antibody or 1 g/ml of the polyclonal anti-green fluorescence protein antibody (CLONTECH, Palo Alto, CA). Precipitates were analyzed by assessing luciferase activity in a luminometer using coelenterazine h as substrate (Molecular Probes, Eugene, OR).…”
Section: Methodsmentioning
confidence: 99%
“…Radioligand Binding Experiments-Whole cell radioligand binding assays were performed as described (13 S binding assays with membranes prepared from HEK 293 cells stably expressing the MT2R as described recently (14).…”
Section: Methodsmentioning
confidence: 99%
“…The latter only weakly stimulates GTP␥S binding because of its tight association with G proteins (15). EGTA-washed cell membranes (ϳ10 g) were suspended in an assay volume of 30 l of buffer containing 25 mM HepesNaOH, pH 7.5, 1.5 mM MgCl 2 , 100 mM NaCl, 1 mM EDTA, and 0.01 mM GDP.…”
mentioning
confidence: 99%